1973
DOI: 10.1128/jb.113.3.1442-1448.1973
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of Cryptococcus neoformans Grown In Vitro as Observed by Freeze-Etching

Abstract: Cryptococcus neoformans grown on culture media was observed by the freeze-etching technique. In the capsule, short fibrils were seen when freezeetched. This organism was unique in the appearance of the cell wall, which showed two strata. The outer one was dense with particles of about 20 nm in diameter, whereas the inner one was sparse in particles. The appearance of the cell membrane of this organism differed distinctly depending on the culture media. When grown on glycerol medium, the cell membrane possessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 9 publications
2
33
0
Order By: Relevance
“…Organisms. C. neoformans strains Okuno and IFO 608 (abbreviated as 608) were used as in vitro (15). They were grown on nonglycerol medium for 2 days at 37 C before inoculation into mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organisms. C. neoformans strains Okuno and IFO 608 (abbreviated as 608) were used as in vitro (15). They were grown on nonglycerol medium for 2 days at 37 C before inoculation into mice.…”
Section: Methodsmentioning
confidence: 99%
“…The in-fected mice were killed 3 to 14 days later, and the lungs or brains were dissected. The dissected tissues were fixed with 5% glutaraldehyde containing 0.067 M phosphate buffer, pH 7.4, for 2 to 3 h at room temperature, and then were immersed in 20 to 40% glycerol for 3 to 5 days at 4 C. Other methods were the same as previously described (15). All the figures in this paper show the freeze-fractured Okuno strain.…”
Section: Methodsmentioning
confidence: 99%
“…A structure suggestive of a nucleus with nuclear pores (Fig. 8) was evident in a few freeze-fracture preparations and indeed does resemble that organelle labeled as a nucleus in recent freeze-fracture preparations of Cryptococcus neoformans (22). If the nucleus were flattened in chlamydospores, it would be difficult to recognize in thin sections, whereas a freeze-fractured preparation would reveal the characteristic pored nuclear surface when fractured in the correct plane.…”
Section: Discussionmentioning
confidence: 63%
“…DISCUSSION Hess and Weber (9) and Takeo (16) showed that some lower fungi have round invaginations on the cell membrane. Takeo (16) revealed that the round invaginations of the cell membrane of Mucor sporangiospore sometimes combine to form a structure resembling rod-like invaginations and suggested that this may be a step toward generation of the rod-like invaginations generally observable in yeast and spore forms of higher fungi (11,13,14,19). Linearization of the round invaginations are also found in Rhizopus sporangiospores, although they are rather rare occurrences.…”
Section: Resultsmentioning
confidence: 99%
“…This is in contrast to the conidiospores of Aspergillus fumigatus. The surface coat of the latter exists from the beginning of spore formation (17). Thus in Aspergillus, the surface coat is not a useful marker of the maturation process.…”
Section: Resultsmentioning
confidence: 99%